2022
DOI: 10.1007/jhep02(2022)191
|View full text |Cite
|
Sign up to set email alerts
|

Spin Matrix Theory in near $$ \frac{1}{8} $$-BPS corners of $$ \mathcal{N} $$ = 4 super-Yang-Mills

Abstract: We consider limits of $$ \mathcal{N} $$ N = 4 super-Yang-Mills (SYM) theory that approach BPS bounds. These limits result in non-relativistic theories that describe the effective dynamics near the BPS bounds and upon quantization are known as Spin Matrix Theories. The near-BPS theories can be obtained by reducing $$ \mathcal{N} $$ N = 4 SYM on a three-sphere and integrating out the fields that become non-dynamical in the limits. In the previ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 72 publications
(166 reference statements)
0
4
0
Order By: Relevance
“…Finally, the one-loop Beisert Hamiltonian in various subsectors has been explored in [75][76][77][78], and dubbed as the "spin matrix theory" that describes the dynamics of near-BPS states. We have shown that the Beisert Hamiltonian takes a very simple form (3.2) and (3.3) in terms of the BPS superfield Ψ, which efficiently organizes all the BPS letters.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the one-loop Beisert Hamiltonian in various subsectors has been explored in [75][76][77][78], and dubbed as the "spin matrix theory" that describes the dynamics of near-BPS states. We have shown that the Beisert Hamiltonian takes a very simple form (3.2) and (3.3) in terms of the BPS superfield Ψ, which efficiently organizes all the BPS letters.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it has been shown that decoupling limits of N = 4 SYM lead to quantum mechanical models, called Spin Matrix Theories (SMT), which have non-relativistic symmetries and are closed under the action of the one-loop dilatation operator [48]. The effective Hamiltonian of these sectors in the near-BPS limit have been derived in [33][34][35][36], leading in some cases to field theory and superfield formulations. It would be interesting to find a link between these decoupling limits of N = 4 SYM and a null reduction JHEP09(2022)237 procedure, and study the quantum properties of both theories.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it does not appear surprising that several investigations of theories which are both supersymmetric and non-relativistic had a great revival in recent years. Starting from the first investigations involving the SUSY generalization of the Galilean algebra and limits of the relativistic models [23][24][25], there have been studies of superconformal anyons [26], spontaneous SUSY breaking [27], the analysis of the renormalization properties of supersymmetric Galilean or Lifshitz-invariant models [28,29], supergravity [30,31] and the study of non-relativistic corners of N = 4 super Yang-Mills (SYM) theory [32][33][34][35][36].…”
Section: Jhep09(2022)237 1 Introductionmentioning
confidence: 99%
“…To further establish this corner of NR strings in the holographic correspondence, this result should also be obtained from a direct quantization of the SMT string sigma model on the FF U (1)-Galilean backgrounds (5.28). Finally, a new approach has recently been developed for the explicit construction of Spin Matrix theories using a classical reduction of N = 4 followed by a suitable quantization and normal ordering procedure [102][103][104][105]. This construction reproduces earlier results obtained [85] from limits of the one-loop spectrum of N = 4 and also leads to a two-dimensional field theory formulation of the SU (1, 1) sectors, suggesting a natural dual description for SMT strings on the threedimensional SU (1, 1) geometry in Table 1 at large N .…”
Section: General Smt String Backgrounds and Penrose Limitsmentioning
confidence: 99%